(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2010)
This study was an attempt to find out the efficacy of pre-emptive analgesia in reducing post-operative pain. Multiple pre-emptive therapies were used in an attempt to see its superiority over single preemption. Pain scores showed significant differences between the pre-emptive and non pre-emptive groups. Pethidine consumed by the pre-emptive non-recipient group was much higher. Patient’s satisfaction was higher and post operative complications were less in the pre-emptive recipient group. Thus pre-emptive multimodal therapy would be better, in reducing post-operative pain, and the amount of post-operative analgesic requirement. It might be concluded that multimodal preemptive therapy by using I/V Ketorolac & Bupivacaine infiltration is an effective method for post operative pain management in maxillofacial surgery. DOI: 10.3329/bjpp.v24i1.5733 Bangladesh J Physiol Pharmacol 2008; 24(1&2) : 17-23